Analisis Pengaruh Kualitas Audit, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Melianis Yuli Purmalita; Fauzan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to examine the influence of audit quality, capital structure, and firm size on firm value in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The sampling technique used in this study is purposive sampling. The data used are secondary data, consisting of annual reports obtained from companies over the four-year period. The data analysis method employed in this study is multiple linear regression analysis. Based on the results of the model feasibility test, the regression model produced is feasible and can be used for further analysis. The results of this study indicate that the significance value of 0.015, which means audit quality significantly affects firm value. The regression coefficient value for capital structure is -0.376 with a significance value of 0.012, indicating that capital structure significantly influences firm value, although the regression coefficient does not positively affect firm value. The coefficient value for firm size is 0.209 with a significance value of 0.122, indicating that firm size partially does not significantly influence firm value, although the regression coefficient positively affects firm value.